Розробка системи для аналізу даних платформи вивчення іноземних мов - Кошарний, Є. Ю. (ХНУРЕ, 2024)
This work is devoted to developing a system aimed at providing a pleasant user experience on a foreign language learning platform while empowering businesses with valuable insights into user behavior. Through comprehensive data analysis, the system enables data-driven decision-making. Leveraging Google Cloud Platform services ensures scalability and efficient handling of user tracking data. Integration of dbt facilitates data transformation for extracting actionable insights. Furthermore, a reporting layer with dashboards, such as Tableau or alternatives, enhances accessibility to the transformed data, facilitating informed decision-making processes. This thesis evaluates the system's efficacy in enhancing user experience and supporting data-driven decisions for businesses.
Keywords: аналіз даних; вивчення іноземних мов